Remodeling the University as an Institution of Choice - YU, Sing Ong (Journal of Research in Educational Sciences; Vol 7 No 9 (2016): Journal of Research in Educational Sciences, 2016)
This paper uses the metaphor of University Remodeling as a framework for analysing students’ choice of a private university and repositioning the university through rebranding of its professors. Remodeling the university involves reconstructing competencies and strengths of the institution. These elements are critical to the growth of the university. Managing growth requires understanding of the factors influencing students’ choice of a university, institutional commitment towards improving these factors, and rebranding the university to differentiate itself from its competitors. The creation of a strong university brand is a strategic issue that requires close collaboration between university administrators and academicians, and should not be left alone to the marketing department.
Keywords: student’ choice; university remodeling; programs; facilities; curricular activities.